PENGARUH MEDIA PEMBELAJARAN CARD SORT TERHADAP PERKEMBANGAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN DI TK AL-MUTTAQIN II - Ridha Maulida; Dwi Septi Anjas Wulan (CV. ADIBA AISHA AMIRA, 2025)
This research is motivated by the presence of children whose early reading development has not developed well and the use of media that is less supportive during the learning process. The study aims to determine the Card Sort Learning Media on the Early Reading Development of Children Aged 5-6 Years in Al-Muttaqin II Kindergarten. This research is a quantitative approach research with an experimental method with a one-group pretest-posttest design. The sample in this study was class B in Al-Muttaqin II which consisted of 20 people with 13 boys and 7 girls using purposive sampling technique. The data collection technique used was observation using instruments. The data analysis technique used was descriptive statistics and inferential statistics. The data obtained were analyzed using the Wilcoxon signed rank test to see the differences in the treatments given. The results of this study showed a significance value of 0.000 <0.05, which means that the Card Sort Learning Media has a significant influence on the Early Reading Development of children aged 5-6 years.